Prognostic impact of CDX2 in stage II colon cancer: results from two nationwide cohorts. Issue 11 (27th November 2018) - Hansen, Torben; Kjær-Frifeldt, Sanne; Eriksen, Ann; Lindebjerg, Jan; Jensen, Lars; Sørensen, Flemming; Jakobsen, Anders
Abstract Background The aim of the present study was to validate the prognostic impact of CDX2 in patients with stage II colon cancer. Methods Two unbiased population-based cohorts representing all patients operated for stage II colon cancer in Denmark in 2002 and 2003. The CDX2 expression was evaluated by immunohistochemistry on whole tumour sections. Patients were classified into three groups, CDX2-positive, -moderate, and -negative, for comparison with the clinical data. Results A total of 1157 patients were included. We found a significant relationship between loss of CDX2 expression and poor disease-free survival in both cohorts, p = 0.0267 and 0.0118, respectively. Five-year disease-free survival rates were 66%, 72% and 74% in the first cohort and 62%, 65%, and 75% in the second cohort for the negative, moderate, and positive CDX2 expression groups, respectively. Multiple Cox regression analysis performed on the combined cohorts confirmed an independent prognostic impact of CDX2 on disease-free survival, hazard ratio 1.543 (95% confidence interval 1.129–2.108), p = 0.0065. Conclusions This retrospective study provides validation regarding the prognostic impact of CDX2 in patients with stage II colon cancer. The results justify prospective validation clarifying its clinical impact.